2023
DOI: 10.3389/fcimb.2023.1284166
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus coagulans prevents the decline in average daily feed intake in young piglets infected with enterotoxigenic Escherichia coli K88 by reducing intestinal injury and regulating the gut microbiota

Yanyan Zhang,
Xiaorong Tian,
Yi Dong
et al.

Abstract: BackgroundEnterotoxigenic Escherichia coli (ETEC), an important intestinal pathogen, poses a significant threat to the intestinal health of piglets. Bacillus coagulans (BC), a potential feed additive, can improve the intestinal function of piglets. However, the effects of BC on growth performance and intestinal function in ETEC-infected piglets are still unclear. In this study, 24 7-day-old piglets were randomly assigned to three treatment groups: control group (fed a basal diet), ETEC group (fed a basal diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…1 Recent studies have identified specific microbial groups and metabolites that show promising results in preventing and controlling ETEC infections. 1,[17][18][19] However, the critical metabolites, their molecular receptors, and the pathways through which these microorganisms exert their effects were previously unclear. Our results have demonstrated that the microbial-derived metabolite SoSa I can effectively protect the host against ETEC infection both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Recent studies have identified specific microbial groups and metabolites that show promising results in preventing and controlling ETEC infections. 1,[17][18][19] However, the critical metabolites, their molecular receptors, and the pathways through which these microorganisms exert their effects were previously unclear. Our results have demonstrated that the microbial-derived metabolite SoSa I can effectively protect the host against ETEC infection both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…14 These compounds demonstrate diverse structures, a broad range of biological activities, including antibacterial, antiviral, and anticancer effects, 15 and play a beneficial role in disease resistance by either directly inhibiting or indirectly stimulating the host defense mechanism. 8,16 Research has shown that during ETEC infections, Bacillus and certain probiotics [17][18][19] metabolize to produce a variety of bioactive small molecules, such as bacteriocin, 10 short-chain fatty acids (SCFAs), 20 and secondary bile acids, 21 which directly or indirectly affect ETEC strains and reduce their colonization in the intestinal tract through different mechanisms. 1 Research by Sudan et al 22 has demonstrated that B. subtilis and its metabolites significantly protect pig intestinal epithelial cells (IPEC-J2) against ETEC infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation